Clinicopathological Characteristics of Serrated Polyposis Syndrome in Korea: Single Center Experience - Hyung-Keun Kim; Kyung-Jin Seo; Hyun Ho Choi; Sung Soo Kim; Hiun-Suk Chae; Ok-Ran Shin; Chang Hyuck Ahn; Young-Seok Cho (Gastroenterology Research and Practice)
Background/Aim. Serrated polyposis syndrome (SPS) is a rare condition characterized by multiple serrated polyps throughout the colon and rectum. The aim of this study was to evaluate the clinicopathological characteristics of SPS in Koreans. Methods. This retrospective analysis of prospectively collected data was performed using information from the endoscopy, clinical records, and pathology database system of Uijeongbu St. Mary’s Hospital. Consecutive patients satisfying the updated 2010 World Health Organization criteria for SPS between June 2011 and May 2014 were enrolled. Results. Of the 17,552 patients who underwent colonoscopies during the study period, 11 (0.06%) met the criteria for SPS. The mean age of these patients was 55.6 years. Ten patients (91%) were males. None had a family history of CRC or a first-degree relative with SPS. Seven patients (64%) had synchronous advanced adenoma. One patient had coexistence of SPS with CRC that was diagnosed at the initial colonoscopy. Five patients (45%) had more than 30 serrated polyps. One of the patients underwent surgery and 10 underwent endoscopic resection. Conclusion. The prevalence of SPS in this study cohort was comparable to that in Western populations. Considering the high risk of CRC, correct diagnosis and careful follow-up for SPS are necessary.